QUALITATIVE ANALYSIS OF GROUP KNOWLEDGE ABOUT ATTITUDES TO MATHEMATICS THROUGH SOCIAL MEDIA REPRESENTATION SOFTWARE - Ardila, Luis Manuel Soto; Caballero, Ana; Alzás, Teresa; VerÃssimo, SofÃa (Cadernos de Educação Tecnologia e Sociedade, 2020)
The present study, based on the Contingency Analysis (Osgood, 2009), pretend to study the attitudes and emotions that a group of 18 professors present towards mathematics and its teaching. The group was asked for some narratives of their experience as students and as teachers. After collecting the narratives of the subjects in the sample, it was analyzed qualitatively, using the webQDA software (Neri de Souza, Costa and Moreira, 2011). Finally, the GEPHI program (Bastian, Heymann and Jacomy, 2009) was used to represent social networks, based on the categories of analysis obtained, which were created automatically and allowed to analyze which were the most important and which were their interrelationships.